Use multiplication or division of power series to find the first three nonzero terms in the Maclaurin series for each function. 5e^(-x)^2 cos(4x)

Respuesta :

Answer:

The first three nonzero terms in the Maclaurin series is

[tex]\mathbf{ 5e^{-x^2} cos (4x) }= \mathbf{ 5 ( 1 -9x^2 + \dfrac{115}{6}x^4+ ...) }[/tex]

Step-by-step explanation:

GIven that:

[tex]f(x) = 5e^{-x^2} cos (4x)[/tex]

The Maclaurin series of cos x can be expressed as :

[tex]\mathtt{cos \ x = \sum \limits ^{\infty}_{n =0} (-1)^n \dfrac{x^{2n}}{2!} = 1 - \dfrac{x^2}{2!}+\dfrac{x^4}{4!}-\dfrac{x^6}{6!}+... \ \ \ (1)}[/tex]

[tex]\mathtt{e^{-2^x} = \sum \limits^{\infty}_{n=0} \ \dfrac{(-x^2)^n}{n!} = \sum \limits ^{\infty}_{n=0} (-1)^n \ \dfrac{x^{2n} }{x!} = 1 -x^2+ \dfrac{x^4}{2!} -\dfrac{x^6}{3!}+... \ \ \ (2)}[/tex]

From equation(1), substituting x with (4x), Then:

[tex]\mathtt{cos (4x) = 1 - \dfrac{(4x)^2}{2!}+ \dfrac{(4x)^4}{4!}- \dfrac{(4x)^6}{6!}+...}[/tex]

The first three terms of cos (4x) is:

[tex]\mathtt{cos (4x) = 1 - \dfrac{(4x)^2}{2!}+ \dfrac{(4x)^4}{4!}-...}[/tex]

[tex]\mathtt{cos (4x) = 1 - \dfrac{16x^2}{2}+ \dfrac{256x^4}{24}-...}[/tex]

[tex]\mathtt{cos (4x) = 1 - 8x^2+ \dfrac{32x^4}{3}-... \ \ \ (3)}[/tex]

Multiplying equation (2) with (3); we have :

[tex]\mathtt{ e^{-x^2} cos (4x) = ( 1- x^2 + \dfrac{x^4}{2!} ) \times ( 1 - 8x^2 + \dfrac{32 \ x^4}{3} ) }[/tex]

[tex]\mathtt{ e^{-x^2} cos (4x) = ( 1+ (-8-1)x^2 + (\dfrac{32}{3} + \dfrac{1}{2}+8)x^4 + ...) }[/tex]

[tex]\mathtt{ e^{-x^2} cos (4x) = ( 1 -9x^2 + (\dfrac{64+3+48}{6})x^4+ ...) }[/tex]

[tex]\mathtt{ e^{-x^2} cos (4x) = ( 1 -9x^2 + \dfrac{115}{6}x^4+ ...) }[/tex]

Finally , multiplying 5 with [tex]\mathtt{ e^{-x^2} cos (4x) }[/tex] ; we have:

The first three nonzero terms in the Maclaurin series is

[tex]\mathbf{ 5e^{-x^2} cos (4x) }= \mathbf{ 5 ( 1 -9x^2 + \dfrac{115}{6}x^4+ ...) }[/tex]

ACCESS MORE